a-Tocopherol and selenium influence on the immune system of piglets - MAVROMATIS (I.X. ΜΑΥΡΟΜΑΤΗΣ) J. H.; KYRIAKIS (Σ.Κ. ΚΥΡΙΑΚΗΣ) S. C.; PAPASTERIADIS (Α. ΠΑΠΑΣΤΕΡΙΑΔΗΣ) A.; KOPTOPOULOS (Γ. ΚΟΠΤΟΠΟΥΛΟΣ) G. (Journal of the Hellenic Veterinary Medical Society, 2018)
Four groups of sows (Μ, Ε. Σ, ΕΣ) of the same genetic background, having equal distribution of the number of parities, living under the same housing conditions and using the same hygienic and nutritional standards, were used in this study. Each group had 12 pregnant sows. The dietary level of a-tocopherol was 20 mg/kg and the Se level 0.45 mg/kg of feed (standard ratio) of the sows in group M during pregnancy an lactation. The sows in group E received the standard ratio, supplemented with 30 mg of a-tocopherol per kg. The sows in group Σ received the standard ratio, but were injected IM with 30 mg Se per sow as sodium selenite on days 30, 60 and 90 of pregnancy. The sows in ΕΣ group received the standard ratio supplemented with 30 mg a-tocopherol per kg and a further three injections IM with Se. The trial started on day 30 of gestation and lasted until weaning day (28 days post farrowing). The conclusion reached through the above study is that the inclusion in the deed of 50 mg of atocopherol per kg and the injectio of pregnant sows with 30 mg of selenium, on standard days, have a positive effect on the immune system of the neonatal and weaned piglets. Furthermore this provides improved live weight gain of the piglet and litter size up to the age of weaning.